Development of a method for modeling the magnetic state and assessing the electromechanical characteristics of a vortex layer of ferromagnetic particles moving in a rotating magnetic field - Polshchikov, Henrikh; Zhukov, Pavlo (Technology audit and production reserves, 2025)
The object of this study is a vortex layer (VL) of ferromagnetic particles (FP) moving in a rotating magnetic field (RMF). Apparatuses vortex layer (AVL) devices are used to intensify energy-intensive technological processes with liquid and bulk materials that require activation, mixing, and fine grinding. External three-phase (380 V/50 Hz) two-pole inductors are used to synthesize the VL in a cylindrical AVL working chamber with a diameter of 60–330 mm. The RMFi modulus of magnetic induction at the bore center in the absence of FP is selected during design from the range of 0.12–0.25 T. Steel or nickel FPs have an elongated cylindrical shape, typically with a ratio of l/d = 8–15 (l is the FP length, d is the FP diameter) and a diameter of 0.7–2.5 mm. The magnetic and electromechanical characteristics of the VL have been insufficiently studied. This paper examines a method for estimating these characteristics of the VL by modeling its magnetic state. A real bipolar RMF existing in a working chamber with an operating VL is represented by the synchronous rotation of three plane-parallel uniform circular vector fields – field strength, induction, and magnetization H, B, J. The experimental determination of the characteristics of the model vectors H, B, J is performed using two flat frame induction coils. The simple behavior patterns of the vector field J are consistent with the relatively chaotic behavior of each individual VL particle. A demonstration example of determining the characteristics of the model vectors H, B, J, the specific torque magnetic moment, the specific power, and the level of chaos of an industrial VL is presented. The results of this work can be used in both academic and engineering applications related to the research and design of AVL and similar equipment.